In vivo imaging of vulnerable plaque with intravascular modalities: its advantages and limitations - Kitahara, Satoshi (Cardiovasc Diagn Ther, 2020)
In vivo imaging of plaque instability has been considered to have a great potential to predict future coronary events and evaluate the stabilization effect of novel anti-atherosclerotic medical therapies. Currently, there are several intravascular imaging modalities which enable to visualize plaque components associated with its vulnerability. These include virtual histology intravascular ultrasound (VH-IVUS), integrated backscatter IVUS (IB-IVUS), optical coherence tomography (OCT), near-infrared spectroscopy and coronary angioscopy. Recent studies have shown that these tools are applicable for risk stratification of cardiovascular events as well as drug efficacy assessment. However, several limitation exists in each modality. The current review paper will outline advantages and limitation of VH-IVUS, IB-IVUS, OCT, NIRS and coronary angioscopy imaging.